A novel brief treatment for methamphetamine use disorders in South Africa: a randomised feasibility trial - Sorsdahl, K.; Stein, D.J.; Pasche, S.; Jacobs, Y.; Kader, R.; Odlaug, B.; Richter, S.; Myers-Franchi, Bronwyn; Grant, J.E. (2021)
Background: Effective brief treatments for methamphetamine use disorders (MAUD) are urgently needed to complement longer more intensive treatments in low and middle income countries, including South Africa. To address this gap, the purpose of this randomised feasibility trial was to determine the feasibility of delivering a six-session blended imaginal desensitisation, plus motivational interviewing (IDMI) intervention for adults with a MAUD.